2018
DOI: 10.1002/jcc.25545
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of large‐gap Si16 clusters encapsulating group‐IV metal atoms (Ti, Zr, Hf)

Abstract: Doped clusters by Si 16 cage encapsulating group-IV metal atoms (M@Si 16 , M = Ti, Zr and Hf) are computationally investigated by both density functional theory (DFT) and high-level CCSD(T) method. Their low-energy structures are globally searched using a genetic algorithm based on DFT. The ground state structures of neutral and anionic M@Si 16 are determined by calculating the vertical and adiabatic detachment energies and comparing them with the experimental data. For neutral Ti@Si 16 , the Frank-Kasper (FK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Our previous studies demonstrated that the HSE06 functional can accurately describe the structural and electronic properties of pristine and metal-doped Si clusters. 37,38 The optical absorption spectra were computed by time-dependent density functional theory (TDDFT). The natural population analysis was conducted using the Natural Bond Orbital (NBO) 3.1 program 39 implemented in the Gaussian 09 package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that the HSE06 functional can accurately describe the structural and electronic properties of pristine and metal-doped Si clusters. 37,38 The optical absorption spectra were computed by time-dependent density functional theory (TDDFT). The natural population analysis was conducted using the Natural Bond Orbital (NBO) 3.1 program 39 implemented in the Gaussian 09 package.…”
Section: Methodsmentioning
confidence: 99%
“…The ground state structures of VSi n clusters were searched independently by our homemade comprehensive genetic algorithm (CGA) code combined with DFT optimization (see S1 of the Supporting Information (SI) for the details of CGA–DFT search). Our previous studies demonstrated that the HSE06 functional can accurately describe the structural and electronic properties of pristine and metal-doped Si clusters. , The optical absorption spectra were computed by time-dependent density functional theory (TDDFT). The natural population analysis was conducted using the Natural Bond Orbital (NBO) 3.1 program implemented in the Gaussian 09 package.…”
Section: Methodsmentioning
confidence: 99%
“…They showed fullerene-like and FK polyhedron structures to be particularly stable. Subsequently a large number of studies have been made and possible suitable metal atom dopants to match the size of 16atom silicon cage have been found to be early transition metals of 3d, 4d, and 5d series, as well as some rare earth metals including Sc, 3 9 1 , 4 0 0 , 4 0 1 , 4 1 8 , 4 3 9 , Ti, 3 5 9 , 3 6 1 , 3 6 4 , 3 6 5 , 3 9 1 , 395,396,401,[410][411][412]418,421,435,461 V, 391,401,425 Cr, 358,364,425 Y, 370,407,472 Zr, 359,361,365,376,386,[410][411][412]421,435,461 Nb, 450 Mo, 358 Hf, 359,365,376,[410][411][412]421,435,461 Ta, 388,426 W, 358,376 La, 408...…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Generally speaking, there are three types of endohedral Si 16 cages: (i) a fullerene-like cage formed by three-coordinated silicon atoms only (isomer a), (ii) FK polyhedron with triangular facets only (Figure 39b) as closo-deltahedron, and (iii) mixed fullerene-FK-like polyhedra with triangular, quadrilateral, pentagonal, or hexagonal facets (Figure 39c, d, e, f). Our calculations confirm the finding from most previous theoretical calculations that fullerene-like cage is energetically favorable for Y, 370,407,472 Zr, 359,361,365,386,[410][411][412]461 La, 408 Hf, 359,365,[410][411][412]461 Ta, 388 and Ho 441,452 dopants. On the other hand, FK polyhedron is the ground state for Sc@Si 16 391 and Ti@Si 16 .…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Although it is difficult to determine the ground state structure by energy in this situation, the 15m2 isomer is the most probable ground state structure based on simulated PES (see below). To our knowledge, only ZrSi 16 - was studied previously by Wu et al [33].…”
Section: Resultsmentioning
confidence: 99%